Transforming Islamic religious education within pesantren: A conceptual framework for integrating deep learning and 21st-century skills - Afelia Friskiana Marzuki; Moh. Zamili (Fakultas Tarbiyah, Universitas Ibrahimy, 2026)
Amid the rapid transformation of modern education, a critical tension has emerged between the pursuit of educational innovation and the preservation of Islamic education’s foundational identity, values, and epistemological framework in responding to contemporary challenges. This study aims to analyze the integration of deep learning as a pedagogical approach in IRE (Islamic Religious Education) in the context of pesantren and examine its contribution to strengthening 21st-century skills while maintaining Islamic values. This study employs a Systematic Literature Review of 18 selected studies from 300 articles (2016–2026), analyzed through thematic analysis and VOSviewer to identify trends in deep learning, 21st-century skills, and Islamic education in pesantren contexts. The results of the study indicate three main themes, namely: (1) deep learning and active pedagogy, (2) 21st-century skills and digital literacy, and (3) Islamic education in the context of pesantren. These findings indicate that deep learning can be integrated into values-based learning in pesantren, particularly in support of the development of students’ critical thinking, creativity, communication, and collaboration skills. However, the implementation of this approach still faces several challenges, such as limited infrastructure, teacher readiness, and resistance to pedagogical change. This study is limited by its reliance on secondary literature from 2016–2026; therefore, future empirical research is needed to validate the application of deep learning in pesantren contexts. This study contributes conceptually by synthesizing the interplay between deep learning, Islamic values, and 21st-century skills, providing a foundation for developing contextual, reflective, and adaptive pesantren learning models aligned with 21st-century educational demands.